Implementation of Project-Based Islamic Education Learning in the Merdeka Curriculum at Albayan Boarding School - Irfan Ilahi Dhohir; Endin Mujahidin; Nesia Andriana (al-Afkar, Journal For Islamic Studies, 2025)
The development of the times requires humans to be adaptive and able to respond to them with actions that are in accordance with human development itself. These changes certainly have an impact on all sectors of life, including education. The government in this case as a policy determinant seeks to make the education process run well in accordance with the mandate of the constitution. The curriculum change policy is a positive response in the face of changing times. Teachers as the spearhead in curriculum implementation are required to play an active role in mastering curriculum changes and be creative in realizing them into an innovative learning process. This study aims to analyze the implementation of the Merdeka Curriculum at Albayan Boarding School, describe the basic concepts of Islamic Education learning, describe project-based learning concepts and analyze the implementation of Islamic Education learning at Albayan Boarding School. This research uses a qualitative descriptive approach using literature studies, observations and interviews as data sources. The research findings show that Albayan Boarding School has implemented a Kurikulum Merdeka for class X (phase E) students. Meanwhile, class XI and XII students still use the previous curriculum, K-13 curriculum. The learning model uses various learning models that facilitate 21st century skills that rely on 4C abilities (critical thinking, collaboration, communication and creative) including project-based learning through photo content and video content. With this learning, it is hoped that it can overcome various kinds of community problems by making iman, devotion and morals begin as the main pillars in making changes.